Prolotherapy as a Novel Adjunct in Post-Stroke Pain Management: A Pilot Study at RSUD Dr. Saiful Anwar Malang - Lestari, Dwi Indriani; Rahmad; Pringga, Gutama Arya; Pambayun, Sheilla Elfira San; Musthafa, Ferdian; Puspitasari, Yuan Laura; Ichsan; Noor, Syeda Tazkia; Zulfikar, Dilloniar Bahny; Ariani, Maydah (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Post-stroke pain (PSP) and musculoskeletal complications significantly hinder recovery and quality of life in stroke survivors. Prolotherapy, a regenerative injection therapy, has shown promise in managing musculoskeletal disorders but remains underexplored for PSP. Aim(s): This study evaluates the effectiveness of prolotherapy in reducing pain, improving range of motion (ROM), and enhancing functional outcomes in PSP patients. Material and methods: This pilot study employed a pre-experimental design with pretest and posttest measurements. Conducted at RSUD Dr. Saiful Anwar Malang, the study included three stroke patients experiencing chronic musculoskeletal pain. Prolotherapy injections containing hypertonic dextrose were administered at regular intervals. Primary outcomes included pain (Numerical Rating Scale), ROM, and spasticity (Modified Ashworth Scale). Secondary outcomes were assessed using the Barthel Index, Short Form-36, and Fugl-Meyer Assessment. Statistical analyses were descriptive, with paired t-tests applied to outcome changes. Result: Significant improvements in pain levels (mean NRS reduction from 5.67±1.5 to 3.0±2.0) and ROM, particularly in shoulder flexion and wrist extension, were observed. Spasticity showed minor improvements in some muscle groups. Functional outcomes, including Barthel Index and SF-36 scores, demonstrated positive trends, with two participants improving from severe dependency to moderate independence. Conclusions: Prolotherapy shows promise as an adjunctive intervention for PSP, offering potential benefits in pain reduction and functional recovery. As the first study of its kind at RSUD Dr. Saiful Anwar Malang, it lays the groundwork for future large-scale research to validate these findings and refine clinical applications. Keywords: Stroke, Prolotherapy, Pain, Rehabilitation, post-stroke pain, functional performance